KRIMINALISASI JUDI ONLINE DALAM PERSPEKTIF KEBIJAKAN HUKUM PIDANA DAN EFEKTIVITAS PENEGAKAN HUKUM DIGITAL DI INDONESIA - Imanuel Inriyanto Ruslak Hammar; Siria Silubun; Mahmud Renuat (PATRIOT, 2026)
Advancements in information and communication technology have brought about significant changes in various aspects of societal life, including the emergence of digital-based gambling practices, or online gambling. Gambling activities that were previously conducted through conventional means can now be accessed via the internet using digital applications, websites, social media, and various electronic transaction instruments. This phenomenon presents new challenges for Indonesia's criminal justice system due to the characteristics of online gambling—namely its transnational nature, anonymity, and reliance on rapidly evolving technology. Beyond causing economic losses, online gambling also has the potential to trigger other criminal offenses such as money laundering and digital fraud, as well as social disruptions affecting families and the community. This research aims to analyze the policy of criminalizing online gambling from the perspective of Indonesian criminal law, examine obstacles to the effective digital law enforcement against online gambling offenses, and formulate an ideal model for addressing online gambling within the framework of modern criminal law policy. The study employs a normative legal research method utilizing statutory, conceptual, and comparative approaches. Legal materials consist of primary sources—specifically legislation and regulations—and secondary sources, including books, scholarly journals, research findings, and various publications related to criminal law and cybercrime. The analysis is conducted using a descriptive-qualitative method. The research findings indicate that the policy of criminalizing online gambling in Indonesia is legally grounded in the Criminal Code (KUHP), the Law on Electronic Information and Transactions (UU ITE), and the Law on the Prevention and Eradication of the Crime of Money Laundering. However, the effectiveness of law enforcement continues to face various obstacles, including the transnational nature of online gambling, the use of offshore servers, anonymous digital transactions, weak technological oversight, and low public legal awareness. Therefore, a more comprehensive mitigation model is required, involving the reformulation of cyber-gambling regulations, the strengthening of digital technology-based law enforcement, the adoption of a "follow-the-money" approach, the enhancement of public digital literacy, and the harmonization of regulations concerning cybercrime and digital financial transactions. This model is expected to improve the effectiveness of criminal law policies in addressing the evolution of online gambling in the digital era.